2020
DOI: 10.1609/aaai.v34i07.6893
|View full text |Cite
|
Sign up to set email alerts
|

Region-Based Global Reasoning Networks

Abstract: Global reasoning plays a significant role in many computer vision tasks which need to capture long-distance relationships. However, most current studies on global reasoning focus on exploring the relationship between pixels and ignore the critical role of the regions. In this paper, we propose an novel approach that explores the relationship between regions which have richer semantics than pixels. Specifically, we design a region aggregation method that can gather regional features automatically into a uniform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Our empirical demonstration showcases several common findings when working with cost-sensitive prediction tasks: as presented in the introduction, benchmark studies have repeatedly shown that no CSL method is always superior on all data sets and with all ML algorithms (Coussement, 2013; Seiffert et al, 2008; Sheng & Ling, 2006). At the same time, no ML algorithm is always superior.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our empirical demonstration showcases several common findings when working with cost-sensitive prediction tasks: as presented in the introduction, benchmark studies have repeatedly shown that no CSL method is always superior on all data sets and with all ML algorithms (Coussement, 2013; Seiffert et al, 2008; Sheng & Ling, 2006). At the same time, no ML algorithm is always superior.…”
Section: Discussionsupporting
confidence: 64%
“…Sheng and Ling (2006) developed a method that also relies on posterior probability estimates, but instead of the exact estimate only the correct order of probabilities is required. This method is called empirical thresholding (ET).…”
Section: In Psychological Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Achieving good predictive performance is challenging in these cases, as algorithms tend to predict the label of the larger classes too frequently. One strategy to address this problem is threshold tuning (Sheng & Ling, 2006). Usually, an observation is classified as belonging to the positive class in a binary classification task if the estimated probability for this observation is greater than 0.5.…”
Section: Discussionmentioning
confidence: 99%
“…Different from skeleton-based action recognition where the skeleton data can be naturally seen as graph structure, generic action recognition methods employ GCNs to model the relations between fixed regions or objects. For example, [4,23,44] adopts GCN to build a reasoning module to model the relations between disjoint and distant regions. [21,48] takes dense object proposals as graph nodes and learns the relations between them.…”
Section: Related Workmentioning
confidence: 99%